2009
DOI: 10.1590/s1415-47572009000300013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-kB 1 (NF-kBp50) by RNA interference in chicken macrophage HD11 cell line challenged with Salmonella enteritidis

Abstract: The NF-kB pathway plays an important role in regulating the immunity response in animals. In this study, small interfering RNAs (siRNA) were used to specifically inhibit NF-kB 1 expression and to elucidate the role of NF-kB in the signal transduction pathway of the Salmonella challenge in the chicken HD11 cell line. The cells were transfected with either NF-kB 1 siRNA, glyceraldehyde 3-phosphate dehydrogenase siRNA (positive control) or the negative control siRNA for 24 h, followed by Salmonella enteritidis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 51 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Gene expression analysis was performed for the selected panel of cytokines: Th1 ( IFNγ , IL12 ), Th2 ( IL4 ), proinflammatory ( IL6 , IL18 , and IL1β ), antiviral ( IFNβ ), and chemokine ( IL8 ). Sequences of primers were based on the literature [19,7376] or designed based on cDNA nucleotide sequence using NCBI Primer Blast [36] (Tab C in S1 File). …”
Section: Methodsmentioning
confidence: 99%
“…Gene expression analysis was performed for the selected panel of cytokines: Th1 ( IFNγ , IL12 ), Th2 ( IL4 ), proinflammatory ( IL6 , IL18 , and IL1β ), antiviral ( IFNβ ), and chemokine ( IL8 ). Sequences of primers were based on the literature [19,7376] or designed based on cDNA nucleotide sequence using NCBI Primer Blast [36] (Tab C in S1 File). …”
Section: Methodsmentioning
confidence: 99%
“…In order to study the role of NF-κB in the signal transduction pathway of the Salmonella enteritidis -challenged cells, chicken macrophage HD11 cell line and small interfering RNAs (siRNA), specifically inhibiting NF-κB1 expression, were used. In particular, it was found that a 36% inhibition of NF-κB1 expression was associated with increased gene expression of both TLR4 and IL-6 at both 1 h and 4 h following Salmonella challenge [ 274 ]. TLR4 was shown to activate NF-κB signaling during cerebral ischemia–reperfusion, leading to increased secretion of inflammatory cytokines and damage of brain tissue [ 275 ].…”
Section: Effect Of Various Stress Factors On Nf-κb Expression and mentioning
confidence: 99%
“…IFNγ can be produced by T helper 1 (Th1) cells and increases the cell-mediated response during an infection, but can be counteracted by IL-10 that has an anti-inflammatory and immune suppressive effect ( Cornelissen et al, 2009 ). NF-κB has a central role in the innate and adaptive immune response toward an infection ( Chiang et al, 2009 ; Oeckinghaus and Ghosh, 2009 ) and activates, amongst others, the production of the cytokine IL-8 ( Liu et al, 2017 ). The lack of difference in transcriptional expression of the selected genes between the 3 hatching systems indicates that with this infection model, the early immune response seems not to be influenced by hatching systems.…”
Section: Discussionmentioning
confidence: 99%
“…Primers used for the gene expression analysis were extracted from literature and annotation is shown in Table 1 . The 6 genes of interest were claudin, occludin ( Gilani et al, 2018 ), nuclear factors Kappa B (NF-κB) ( Chiang et al, 2009 ). IL8, interferon gamma (IFNγ) ( Cornelissen et al, 2009 ), and IL10 (Genbank accession nr.…”
Section: Methodsmentioning
confidence: 99%